A theory of pruning - Giovanni Lombardo; Harald Uhlig (European Central Bank (ECB), 2014)
Often, numerical simulations for dynamic, stochastic models in economics are needed. Higher order methods can be attractive, but bear the danger of generating explosive solutions in originally stationary models. Kim-Kim-Schaumburg-Sims (2008) proposed pruning to deal with this challenge for second order approximations. In this paper, we provide a theory of pruning and formulas for pruning of any order. We relate it to results described by Judd (1998) on perturbing dynamical systems.
Keywords: C63; C02; C62; 330; numerical economics; numerical simulation; Perturbation Methods; pruning; Taylor expansion